Evaluation Study of the High Yielding Varieties Programme Volume - I - Planning Commission (Planning Commission, 1968)
A study was undertaken by the P.E.O, regarding the implementation of the high yielding varieties programme during 1967-66. The report covering four kharif crops viz. paddy, maize, bajra and jowar, was presented in two parts. For the rabi season, in view of the- importance of wheat crop and the tremendous response the programme received, it was considered appropriate to bring out a separate report for this crop. The data for the other rabi crops will be presented in the fourth and final report for the year. The study for wheat was carried out in 15 districts in as many as 6 States covering a sample of 441 participant and 192 non-participant cultivators. In order to collect complete and accurate data, the study was carried out in three rounds of field visits to selected areas and cultivators. The aspects covered in the study included planning, programming, organisation of supplies and credit, extent of adoption of various recommended, improved practices and inputs, cultivation expenses, levels of yields, extent of acceptance of the high yielding varieties among the cultivators and the problems thereto for wider adoption.
Programme Evaluation Organisation Planning Commission Government of India